Preparation method of thick electrode
By doping porous support materials, such as aerogels, the problem of void damage during the rolling process is solved, the energy density and charge transfer rate of the battery are improved, and the battery manufacturing process is simplified.
Patent Information
- Application Number
- CN202411278007.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art voids in thick electrodes are easily crushed or compressed into discontinuous during the rolling process, resulting in difficulty in ion transmission and affecting the energy density and performance of the battery.
Doping porous support materials, such as aerogels, in thick electrodes, provides electrolyte transfer paths and supports voids to prevent them from being damaged during rolling. It is mixed with the electrode material by wet and dry preparation methods and compacted .
It effectively improves the energy density of the battery and the liquid retention volume of the electrode sheet, maintains the stability of the gap, improves the interface contact between the electrode and the electrolyte, reduces the interface impedance, increases the charge transfer rate, and simplifies the battery manufacturing process.
Smart Images

Figure CN119170747A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a method for preparing a thick electrode. Background Art
[0002] With the widespread application of lithium-ion batteries, the market has put forward new requirements for the energy density of lithium-ion batteries. At present, the progress of the material segment is relatively slow. The design of battery cell parameters is particularly important for improving the energy density of battery cells. Under certain capacity conditions, increasing the electrode coating load can reduce the amount of materials such as current collectors and diaphragms, thereby improving the energy density of the battery cell. In addition, the thick electrode strategy has good compatibility with other strategies for improving energy density, has wide adaptability, and is universal;
[0003] However, one of the performance issues that the thick electrode strategy has to solve is the transmission of lithium ions in the thick electrode, which requires the electrode to have good enough wettability to provide the electrolyte retention rate in the electrode. The typical strategy is to reduce the tortuosity of the electrode. At present, there are many patents that reflect the reduction of the tortuosity of thick electrodes.
[0004] For example, a method for preparing a thick electrode based on a dry film-making process is proposed in the publication number CN117936686A, which uses dry slurry to add a pore-forming agent to the electrode piece, and then uses heating and other methods to decompose the pore-forming agent into gas, leaving a pore size for increasing the amount of liquid retention in the gas path, and then uses a leveling agent to improve the flatness of the electrode piece and the bonding force of the electrode piece to obtain the final thick electrode;
[0005] A method for manufacturing a negative electrode sheet of a lithium battery proposed in the publication number CN116864631A combines magnetic material and gradient coating method, adds magnetic material during the homogenization process, and the coated negative electrode slurry is first sucked out of the magnetic device by an adsorption device and then dried, finally obtaining a low-tortuous thick electrode negative electrode sheet;
[0006] A method for preparing a thick lithium iron phosphate electrode proposed in publication number CN117525303A improves the rolling cracks of the electrode by pre-drying the electrode and adding multi-walled carbon nanotubes, and improves the charge transfer impedance, but does not improve the ion transfer impedance;
[0007] The preparation method of the negative electrode sheet of a lithium ion battery and its application in a lithium ion battery proposed in the publication number CN117613201A adopts a gel method to prepare an electrode, and then freeze-dries the gel electrode to manufacture a thick electrode;
[0008] In addition to the above patents, some patents also use gradient gaps to improve the ion transport performance of thick electrodes;
[0009] The disadvantages of the above patents and prior art are that the gaps are mostly air paths or gaps, which cannot support the subsequent rolling. In the subsequent rolling process, the gaps are very likely to be narrowed or pressed into discontinuous gaps, resulting in difficulty in ion transmission in the part close to the current collector.
[0010] Therefore, it is necessary to propose a new method for preparing thick electrodes. Summary of the invention
[0011] The purpose of the present invention is to provide a method for preparing a thick electrode, which can dope a porous supporting material into the thick electrode to provide an electrolyte transmission path while ensuring support for the gaps to prevent the gaps from being crushed or discontinuously pressed during the rolling process.
[0012] The technical solution adopted by the present invention is as follows:
[0013] A method for preparing a thick electrode includes a wet electrode preparation method and a dry electrode preparation method. In both methods, a porous supporting material is doped into an electrode material to prepare a thick electrode comprising at least one porous supporting material electrode layer.
[0014] The wet electrode preparation method comprises the following steps:
[0015] S1: slurry preparation, mixing the electrode material with the porous support material;
[0016] S2: coating, spreading the electrode material on the current collector;
[0017] S3: Drying, drying the NMP or water in the electrode;
[0018] S4: rolling to compact the thick electrode.
[0019] The dry electrode preparation method comprises the following steps:
[0020] A1: Drying of raw materials, drying of moisture in electrode materials and porous support materials;
[0021] A2: fibrillation treatment to fibrillate the binder in the electrode material;
[0022] A3: Dry electrode film pressing, pressing the electrode material into a uniform and continuous electrode film;
[0023] A4: Compound the current collector and the electrode film to form a thick electrode.
[0024] The technical effects achieved by the present invention are:
[0025] The present invention can dope the porous support material into the thick electrode, provide an electrolyte transmission path, and ensure support for the voids, thereby preventing the voids from being crushed or discontinuously pressed during the rolling process. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the wet thick electrode manufacturing process of the present invention;
[0027] Figure 2 It is a schematic diagram of the dry thick electrode production process of the present invention. DETAILED DESCRIPTION
[0028] In order to make the purpose and advantages of the present invention more clearly understood, the present invention is specifically described below in conjunction with embodiments. It should be understood that the following text is only used to describe one or several specific embodiments of the present invention, and does not strictly limit the scope of protection of the specific claims of the present invention.
[0029] like Figure 1-2 As shown, a method for preparing a thick electrode includes a wet electrode preparation method and a dry electrode preparation method. In both methods, a porous support material is doped into an electrode material to prepare a thick electrode comprising at least one porous support material electrode layer, which provides an electrolyte transmission path while ensuring support for the voids to prevent the voids from being crushed or discontinuously pressed during the rolling process;
[0030] The porous support material is an aerogel, and the aerogel includes one or more of graphene aerogel, carbon dot aerogel, and hard carbon nanofiber aerogel;
[0031] Furthermore, the electrode material is composed of one or more of lithium iron phosphate, a conductive agent, a binder and a dispersant.
[0032] Furthermore, the conductive agent comprises one or more of conductive carbon black and CNT;
[0033] The binder comprises one or more of PVDF and PTFE;
[0034] The dispersant comprises one or more of a polyester and a polyether dispersant containing a polar group;
[0035] When wet electrode is used, NMP is used as dispersant, and the solid content is 55% to 65%.
[0036] Since thickening the electrode based on the prior art will affect the ion conductivity of the material near the current collector, the present invention enhances the ion transmission performance of the thick electrode by adding aerogel to the electrode to increase its liquid retention capacity.
[0037] The present invention comprises at least one specific aerogel concentration electrode layer, may comprise two or more aerogel concentration electrode layers, and may also comprise an aerogel concentration gradient electrode layer.
[0038] To illustrate the method for preparing the thick electrode in the present application, the present application proposes a plurality of embodiments as follows:
[0039] Embodiment 1:
[0040] See attached Figure 1 As shown, the wet electrode preparation method comprises the following steps:
[0041] S1: slurry preparation, mixing the electrode material with the porous support material;
[0042] Further, the amount of lithium iron phosphate is between 94.0% and 97.0%, the amount of conductive carbon black is between 0.5% and 2.0%, the amount of CNT is between 0% and 0.5%, the amount of PVDF is between 0% and 2.0%, the amount of PTFE is between 0% and 2.5%, the amount of aerogel is between 0% and 1.0%, and the amount of dispersant is between 0% and 0.2%;
[0043] S2: coating, spreading a specific amount of electrode material on the current collector;
[0044] The current collector is preferably aluminum foil. The wet electrode is coated once or multiple times by slit coating to achieve a thick electrode of a specific thickness. The thickness of a single side of the electrode is 10 to 1000 μm. The thickness of the aluminum foil is 10 to 50 μm;
[0045] S3: Drying, drying the NMP or water in the electrode to prevent problems such as sticking to the roller in the subsequent process;
[0046] The oven should be a multi-section oven, and the oven temperature should be slowly increased, kept at a constant temperature, and slowly cooled from front to back. The constant temperature should be less than 120°C, and the temperature out of the oven should be less than 55°C;
[0047] S4: rolling, compacting the thick electrode to ensure contact and conductivity between its particles;
[0048] The compaction is affected by the material properties of the selected lithium iron phosphate, the amount of aerogel added and the current collector performance. Preferably, the compaction should be controlled between 2.35 and 2.65 g / cm3;
[0049] Specifically, this embodiment operates according to the following description:
[0050] The materials were mixed according to the following ratio: LFP:SP:CNT:PVDF:graphene aerogel:dispersant=96.3:0.5:0.5:2.0:0.5:0.2.
[0051] The solid content is 60%, the solvent is NMP, the homogenization method is wet homogenization, the coating single-side load is 200mg / cm2, the oven uses a six-section oven, each section is 3 meters, the maximum oven temperature is 110℃, and the oven outlet temperature is 55℃. The compacted density is 2.5g / cm3.
[0052] Embodiment 2:
[0053] See attached Figure 2 As shown, the dry electrode preparation method comprises the following steps:
[0054] A1: Drying of raw materials, drying of moisture in electrode materials and porous support materials;
[0055] Preferably, the raw material drying temperature is less than 100°C and the drying time is less than 8h, wherein the present embodiment does not use a dispersion liquid;
[0056] A2: fibrillation treatment, fibrillating the binder in the electrode material under high-speed shearing, especially fibrillating PTFE;
[0057] Through this step, it can produce adhesion to other materials and form a self-supporting film during the extrusion process. The fibrillation shear rate is 100-2000rmp, the time is 10-60min, and the standing time after shearing is 0-120min;
[0058] A3: Dry electrode film pressing, pressing the electrode material into a uniform and continuous electrode film;
[0059] Among them, the roller speed is 1-5m / min, the pressing temperature is 60-110°C, and the pressure is 1-10 tons;
[0060] A4: Compound the current collector and the electrode film to form a thick electrode;
[0061] The compounding temperature is between 90 and 120°C and the pressure is between 20 and 50 tons;
[0062] Specifically, this embodiment operates according to the following description:
[0063] The dried materials were mixed according to the following ratio: LFP:SP:CNT:PTFE graphene aerogel = 96.2:0.5:0.5:2.3:0.5.
[0064] Ball milling was performed at a speed of 300 rpm for 5 minutes, followed by resting for 1 minute, and repeated five times to complete the fibrillation treatment. The material was then subjected to hot roller pressing, with a roller press speed of 1 m / min, a pressure of 5 tons, and a surface density of 350 mg / cm2. The current collector and the dry electrode were then hot pressed. At 120°C and a pressure of 50 tons, the dry electrode film was composited with the current collector to obtain a dry electrode.
[0065] The above two embodiments can achieve the following effects:
[0066] The energy density of the battery can be effectively improved, and the gap stability of the thick electrode during the rolling process and the cycle process can be effectively maintained, the liquid retention and wettability of the electrode can be improved, and the interface contact between the electrode and the electrolyte can be effectively improved, the interface impedance can be reduced, and the charge transfer rate of the battery can be increased. The strong liquid absorption performance of the aerogel provided by the method can simplify the liquid injection process in battery manufacturing, reduce the number of vacuuming and pressurizing, and improve production efficiency. It has good compatibility with existing equipment and methods, and can complete cutting at low cost.
[0067] In order to illustrate that the porous support material added in the present application has advantages over other thick electrodes, the present application also proposes a comparative example, namely Example 3, in which the porous support material is not added, and the method is as follows:
[0068] Embodiment 3:
[0069] The materials were mixed in the following ratios: LFP:SP:CNT:PVDF:dispersant=96.8:0.5:0.5:2.0:0.2;
[0070] The solid content is 60%, the solvent is NMP, the homogenization method is wet homogenization, and the other methods are the same as those in Example 1.
[0071] When comparing the climbing heights in Examples 1-3, refer to the following table:
[0072] Example Climbing height / cm Example 1 5.213 Example 2 6.409 Example 3 1.712
[0073] Note: The above table shows the climbing height of the pole piece in DMC;
[0074] The above table shows the climbing height data of three types of electrodes in DMC. The test method is to cut the electrode into 5cm wide and 30cm long pieces. Hang the thick electrode, soak the bottom 3cm in DMC, and observe the liquid absorption height of the electrode after 30 minutes;
[0075] When comparing the liquid retention amounts in Examples 1-3, see the following table:
[0076] Example Liquid retention / g Example 1 2.637 Example 2 3.013 Example 3 1.815
[0077] Note: The above table shows the amount of liquid retained by the electrode in DMC;
[0078] The table above shows the liquid retention of three types of electrodes in DMC. The test method is to weigh 10.00g of the electrode, soak it in DMC for 2 hours, take it out, and place it in the air until no drop of liquid drips within 5 minutes, weigh and record the weight w (g), and the liquid retention is w minus the initial weight.
[0079] Through the climbing height and liquid retention rate of the electrode in DMC in the above two tables, it can be concluded that the electrode with added graphene aerogel has better wetting performance and liquid retention in DMC.
[0080] Since the aerogel material has a certain volume, it can occupy a certain space when introduced into a thick electrode. At the same time, it has a high liquid absorption, so it can occupy a certain space and conduct ions at the same time. Aerogel has a strong compressive resistance when it is smaller in volume, and can stably provide pores for transmitting liquid. The concentrated aerogel listed in this article does not react with materials and electrolytes, and some aerogels are conductive. The performance of the original system can be guaranteed.
[0081] The above is only a preferred embodiment of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principles of the present invention, and these improvements and modifications should also be considered as the protection scope of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention shall be implemented according to the conventional means in the art unless otherwise specified and limited.
Claims
1. A method for preparing a thick electrode, Features: The preparation method includes a wet electrode preparation method or a dry electrode preparation method. In both methods, a porous supporting material is doped into an electrode material to prepare a thick electrode comprising at least one porous supporting material electrode layer.
2. A method for preparing a thick electrode according to claim 1, Features: The wet electrode preparation method comprises the following steps: S1: slurry preparation, mixing the electrode material with the porous support material; S2: coating, spreading the electrode material on the current collector; S3: Drying, drying the NMP or water in the electrode; S4: rolling to compact the thick electrode.
3. A method for preparing a thick electrode according to claim 2, Features: The dry electrode preparation method comprises the following steps: A1: Drying of raw materials, drying of moisture in electrode materials and porous support materials; A2: fibrillation treatment to fibrillate the binder in the electrode material; A3: Dry electrode film pressing, pressing the electrode material into a uniform and continuous electrode film; A4: Compound the current collector and the electrode film to form a thick electrode.
4. A method for preparing a thick electrode according to claim 1, Features: The electrode material consists of one or more of lithium iron phosphate, a conductive agent, a binder and a dispersant.
5. A method for preparing a thick electrode according to any one of claims 2 or 3, Features: The porous supporting material is aerogel.
6. A method for preparing a thick electrode according to claim 5, Features: The aerogel is composed of one or more of graphene aerogel, carbon dot aerogel and hard carbon nanofiber aerogel.
7. A method for preparing a thick electrode according to claim 3, Features: The drying temperature in A1 is less than 100° C., and the drying time is less than 8 hours.
8. A method for preparing a thick electrode according to claim 3, Features: The compounding temperature in A4 is between 90 and 120° C., and the pressure is between 20 and 50 tons.
Citation Information
Patent Citations
High-rate thick electrode and preparation method and application thereof
CN110010900A
Long-cycle-life lithium ion battery and preparation method thereof
CN113809385A
Method for preparing thick electrode based on dry method membrane preparation process
CN117936686A
Electrodes for energy storage devices
US20240097134A1
Gel polymer lithium ion capacitor battery and electrode, and preparation method therefor
WO2022134377A1
Cited By
Zinc ion manganese-based thick electrode preparation method based on laser micro-nano regulation and battery
CN121641815A
